Pengaruh Budaya Organisasi Terhadap Kinerja Personel Polisi Di Polsek Tlanakan Kabupaten Pamekasan Yang Dimediasi Oleh Kompensasi - Sutikno Sutikno; Chamariyah Chamariyah; Wasis Budiarto (Journal of Management and Creative Business, 2024)
This type of research is explanatory, namely research that tests hypotheses between hypothesized variables that will be tested. using a quantitative approach, the research sample was 35 respondents. In this study the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To test and analyze the significant influence of organizational culture on the performance of police personnel. 2) To test and analyze the significant effect of organizational culture on compensation. 3) To test and analyze the significant effect of compensation on the performance of police personnel 4) To test and analyze the significant effect of organizational culture on the performance of police personnel. The results showed that: 1) Organizational culture has a positive and significant effect on the performance of police personnel. This is evidenced by the original sample value of 0.255 and p-values of 0.039. 2) Organizational culture has a positive and significant effect on compensation. This is evidenced by the original sample value of 0.439 and p-values of 0.001. 3) Compensation has a positive and significant effect on the performance of police personnel. This is evidenced by the original sample value of 0.371 and p-values of 0.046. 4) Organizational culture has a positive and insignificant effect on the performance of police personnel mediated by compensation. This is evidenced by the original sample value of 0.163 and p-values of 0.129.